Аналіз високочастотної модуляції несучих гармонік періодично нестаціонарного випадкового сигналу - Яворський, І.М.; Юзефович, Р.М.; Личак, О.В. (Доповіді НАН України, 2022)
Проведено аналіз кореляційних і спектральних властивостей періодично нестаціонарного випадкового сигналу (ПНВС), несучі гармоніки якого модульовані за амплітудою та фазою високочастотними стаціонарно
зв’язаними випадковими процесами. Показано, що кореляційні функції сигналу та його перетворення
Гільберта є однаковими, а їх взаємокореляційні функції мають протилежні знаки. Отримано представлення вузькосмугового ПНВС у вигляді стаціонарних, але періодично-нестаціонарно зв’язаних компонент. Показано можливості виділення й аналізу їх квадратур з використанням перетворення Гільберта. The covariance and spectral properties of the periodically non-stationary random signals (PNRS), whose carrier
harmonics are high-frequency modulated by jointly stationary processes are analyzed. It is shown that the
covariance functions of this PNRS and its Hilbert transform are the same and their cross-covariance functions
have different signs. The representation of the narrow-band PNRS in the form of a superposition of the stationary,
but jointly periodically non-stationary components is obtained. The Hilbert transforms of this representation are
analyzed, and the formulae for the Fourier coefficients for the covariance function of an analytic signal are derived.
These formulae show their dependences on auto- and cross-covariance functions of the narrow-band component
quadratures. It is shown that such quadratures can be extracted and analyzed using the Hilbert transform.